INVESTASI UANG ZAKAT OLEH LEMBAGA ZAKAT MENURUT PANDANGAN ISLAM - Muhammad Firdaus (FEBI IAIN Langsa, 2016)
The objective of this study is to examine the concept of investment of zakat money, which is permitted in Islam based on the teachings of the scholars. Data for the study were obtained from content analysis of the injunctions related to investment of zakat money. The result of the study shows that only the surplus amount of zakat money of the current year, that cannot be distributed, can be invested. Scholars have different views as regards to such investment. Some of the views support investing zakat money whereas, other are against such investment. Nevertheless, those who permit investment of zakat money have provided certain guidelines to be followed in order to protect the recipients' interest, due to risks involved in investment or management vulnerability.